The medicinal mushroom Ganoderma lucidum prevents lung tumorigenesis induced by tobacco smoke carcinogens - Shahid, Ayaz; Chen, Mengbing; Yeung, Steven; Parsa, Cyrus; Orlando, Robert; Huang, Ying (Frontiers in Pharmacology, 2023)
Ganoderma lucidum (GL), commonly known as "Lingzhi", is a well-known medicinal mushroom with antioxidant and anti-cancer activity. This study examined the effects of a commercial GL product (GLSF) containing the spore and fruiting body in a 30:8 ratio on tobacco smoke carcinogen-induced lung toxicity and carcinogenesis. The potential chemopreventive effect of GLSF was evaluated in vitro and in vivo. The non-tumorous human bronchial epithelial cells (BEAS-2B cells) were treated with GLSF extract (0.025 and 0.05 mg/mL), which significantly blocked malignant transformation induced by benzo[a]pyrene diol epoxide (BPDE) in a dose-dependent manner. To confirm its anticarcinogenic activity in vivo, the mice were pre-treated with GLSF (2.0 g/kg of body weight) or curcumin (100 mg/kg of body weight) by oral gavage daily for 7 days and then exposed to a single dose of benzo[a]pyrene (B[a]P) (125 mg/kg of body weight). The GLSF-treated mice showed a significant reduction in B[a]P-induced lung toxicity, as indicated by decreased lactate dehydrogenase activity, malondialdehyde levels, inflammatory cell infiltration, and improved lung histopathology. We next determined the chemopreventive activity of GLSF in mice which were exposed to two weekly doses of 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK, 100 mg/kg, on the 1 st and 8 th days) and fed with control or a modified diet containing GLSF (2.0 g/kg) or metformin (250 mg/kg) for 33 weeks. The GLSF and metformin treatments blocked NNK-induced lung tumor development by decreasing the lung weight, tumor area, and tumor burden compared to the mice exposed to NNK only. GLSF treatment also attenuated the expression of inflammatory, angiogenic, and apoptotic markers in lung tumors. Therefore, GLSF may be used for ameliorating tobacco smoke carcinogens-induced lung toxicity and carcinogenesis.